Efektifitas Pertumbuhan Dan Produksi Jamur Tiram (Pleorotus osteorotus) Sebagai Respon Dari Macam Dan Dosis Moodbooster Pada Baglog - Sulistiyowati, Retno; Rizaldi, Hadi; Hartanti, Aprilia (Agrotechbiz : Jurnal Ilmiah Pertanian, 2023)
Oyster mushroom is a type of wood fungus that originally grew naturally on tree trunks that had undergone weathering in forest areas. To increase the production of white oyster mushrooms, have to added nutrients from outside in the form of mood boosters as a supporting ingredient for growing media. This study used a Factorial Randomized Block Design (RBD) with two factors. The first factor is various mood booster: rice washing water, coconut water, and sugar water. The second factor is mood booster dose: 0 ml / baglog, 50 ml / baglog, 100 ml / baglog and 150 ml / baglog. Based on the results, it can be concluded as follows: (1) The treatment of various mood booster rice water has effective in providing the best results on the parameters of the number of hoods and fruit weight, (2) Mood booster dose treatment of 100ml/baglog gave the best effects on the parameters of mycelium fulfillment time, pinhead emergence time, fruit weight, and the number of white oyster mushroom hoods, (3) there was an interaction between the rice water mood booster and the 100 ml/baglog mood booster dose against all parameters. Keywords : Oyster mushrooms, various mood booster, mood booster dosage